ANALISIS PEGALAMAN NASABAH KREDIT TERHADAP LOYALITAS (STUDI KASUS PADA KOPERASI PERDANA JAYA UTAMA) - Try Wahyu Ramadhan; Muhajirin (Pusat Riset dan Publikasi, 2022)
The cooperative, which has been operating for 7 years, has experienced many ups and downs, but this cooperative is still able to survive in the midst of today's increasingly competitive financial and economic world. The Perdana Jaya Utama Cooperative is here by prioritizing services to people who need credit loans. Basically, this credit provision is given to customers who need loans, but along with the number of bad credit cases that occur, the cooperative also chooses prospective customers. Creating a customer satisfaction experience is an effective thing for banking companies in Indonesia in achieving competitive advantage and increasing customer loyalty. The population used in this study were customers who made credit to the Perdana Jaya Utama cooperative, amounting to 300 people with a total sample of 171 people. The analytical technique used is the correlation coefficient test and the coefficient of determination, multiple regression test and T test. In this study, a value of 0.590 was obtained. This shows that loyalty (Y) is influenced by customer experience by 59% while the remaining 41% is influenced by other factors. while the T test proves that the experience of customers in doing credit at the Perdana Jaya Utama cooperative can affect their loyalty.